2014
DOI: 10.1016/j.celrep.2014.06.005
|View full text |Cite
|
Sign up to set email alerts
|

S-Nitrosylation-Mediated Redox Transcriptional Switch Modulates Neurogenesis and Neuronal Cell Death

Abstract: SUMMARY Redox-mediated posttranslational modifications represent a molecular switch that controls major mechanisms of cell function. Nitric oxide (NO) can mediate redox reactions via S-nitrosylation, representing transfer of an NO group to a critical protein thiol. NO is known to modulate neurogenesis and neuronal survival in various brain regions in disparate neurodegenerative conditions. However, a unifying molecular mechanism linking these phenomena remains unknown. Here we report that S-nitrosylation of my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
78
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(82 citation statements)
references
References 55 publications
(96 reference statements)
3
78
0
Order By: Relevance
“…A thiol-disulfide redox switch in the Rev-erbβ molecule appears to control the interaction between heme and the ligandbinding domain, with the reduced form exhibiting an affinity which is 5-fold higher than that of the oxidized form [9]. Moreover, Okamoto et al have demonstrated that the muscle-specific transcription factor myocyte enhancer factor 2 (MEF2) can undergo NO-induced nitrosylation, which disrupts MEF2-DNA binding and the transcriptional activity [10]. Specifically, MEF2 dimerization creates a pocket that facilitates S-nitrosylation of an evolutionally conserved cysteine residue in the DNA binding domain.…”
Section: Editorialmentioning
confidence: 99%
See 2 more Smart Citations
“…A thiol-disulfide redox switch in the Rev-erbβ molecule appears to control the interaction between heme and the ligandbinding domain, with the reduced form exhibiting an affinity which is 5-fold higher than that of the oxidized form [9]. Moreover, Okamoto et al have demonstrated that the muscle-specific transcription factor myocyte enhancer factor 2 (MEF2) can undergo NO-induced nitrosylation, which disrupts MEF2-DNA binding and the transcriptional activity [10]. Specifically, MEF2 dimerization creates a pocket that facilitates S-nitrosylation of an evolutionally conserved cysteine residue in the DNA binding domain.…”
Section: Editorialmentioning
confidence: 99%
“…Specifically, MEF2 dimerization creates a pocket that facilitates S-nitrosylation of an evolutionally conserved cysteine residue in the DNA binding domain. This redox switch inhibits neurogenesis and neuronal survival, and it is suggested that this may be an important molecular mechanism to explain the effects of NO in neurodegenerative diseases [10].…”
Section: Editorialmentioning
confidence: 99%
See 1 more Smart Citation
“…2 E and F). Our group has previously shown-via reporter gene assays, chromatin immunoprecipitation (ChIP), and electrophoretic mobility shift assay-that posttranslational redox modification of Cys39 inhibits MEF2 transcriptional activity by interfering with DNA binding (27,28,35,36). Hence, it might be expected that excessive ROS exposure would lead to the formation of SO X H-MEF2D (x = 1-3), thereby impairing transcription of MEF2 target genes.…”
Section: Mef2dmentioning
confidence: 99%
“…Mechanistically, we show that excessive ROS in this LIRD model leads to decreased MEF2 activity via a posttranslational modification of MEF2 at cysteine 39 (causing a sulfonation adduct). The presence of this adduct interferes with the ability of the transcription factor to bind to DNA (27,28), thus preventing activation of its downstream targets. We show that heterozygosity for Mef2d partially decreases MEF2D transcriptional activity, rendering photoreceptors more susceptible to an oxidizing light insult.…”
mentioning
confidence: 99%